A rare case of avascular necrosis of the hip joint secondary to ochronosis (Indian Journal of Case Reports, 2024)
This is a case report of a 53-year-old female patient who presented with long-standing hip pain secondary to avascular necrosis of the hip joint. She underwent total hip replacement and her intraoperative findings raised suspicion of ochronosis and was retrospectively evaluated for alkaptonuria both clinically and through biochemical investigations to confirm the diagnosis.